El derecho de visitas de las personas privadas de libertad frente a los niños, niñas y adolescentes en la legislación Ecuatoriana - Fernanda Magaly, Fernández Parra (2019)
The investigation titled “Postural Hygiene for preventing spine disorders in the National University of Chimborazo, 2019” Its objective was to execute a Postural Hygiene Plan during established work hour activities by the National University of Chimborazo staff for preventing future injuries or disorders at the level of the spine in 2019 period. Thirty people participated as the simple. They were part of the administrative área who worked for Political Science, College, and DTIC. For collecting data, the methodology used was quasi-experimental of a qualitative with and applied, an observational, a descriptive